Prevalence of dry eye disease in Russia - O.N. Onufriichuk; A.V. Kuroyedov (РМЖ "Клиническая офтальмология", 2021)
O.N. Onufriichuk1, A.V. Kuroyedov2,3 1G.I. Turner National Medical Research Center for Сhildren’s Orthopedics and Trauma Surgery, St. Petersburg, Russian Federation 2P.V. Mandryka Military Clinical Hospital, Moscow, Russian Federation 3Pirogov Russian National Research Medical University, Moscow, Russian Federation Dry eye disease (DED) is common in the general population, and the number of patients is growing. Several risk factors including the COVID-19 pandemic and associated ubiquitous personal protective equipment (such as eye wear or face mask) wearing and distance learning and telework contribute to this process. This disease more and more affects the quality of life and labor productivity. However, the prevalence of DED in Russia is understudied while the studies vary in quantity and quality thus preventing the compilation of data and their extrapolation on the general population. This issue is further exacerbated by the lack of study coordination in a whole country and, as a result, the use of different methods and diagnostic criteria, samples of unequal age, comorbidities, region, and climatic geographical living conditions. This review paper attempts to summarize major trends and issues and to outline ways to study and solve them. Keywords: dry eye disease, DED, prevalence, epidemiology, tear, ocular surface. For citation: Onufriichuk O.N., Kuroyedov A.V. Prevalence of dry eye disease in Russia. Russian Journal of Clinical Ophthalmology. 2021;21(2):96–102. DOI: 10.32364/2311-7729-2021-21-2-96-102.